Alibaba: The House that Jack Ma Built - Clark, Duncan; Aneet (Gyan Management Journal, 2018)
Jack Ma, a man from modest beginnings, in just a decade and a half, started out as an English teacher, founded Alibaba and built it into one of the world’s largest companies, an e-commerce empire on which hundreds of millions of Chinese consumers depend. In 2014, Alibaba’s 2 5 billion IPO was the largest global IPO in history. A Rockefeller of his time, who is courted by CE Os and presidents around the world, Jack is an icon for China’s booming private sector and the gatekeeper to hundreds of millions of middle-class consumers.The author, Duncan Clark first met Jack in 1999 in the small apartment where Jack founded Alibaba. The author draws on his own experience as an early adviser to Alibaba and his two decades in China chronicling the Internet’s impact on the country to create an authoritative, compelling narrative account of Alibaba’s rise.